Adsorption Behavior of Trimethylolpropane‐Dehydroabietic Acid Ester at the Air–water Interface. Issue 6 (12th September 2016) - Zhou, Juying; Yang, Yanping; Liang, Yuyan; Lei, Fuhou; Xu, Haitang; Lu, Jianfang; Zhao, Yanzhi; Zhou, Yan
Abstract: A novel amphipathic trimethylolpropane‐dehydroabietic acid ester was successfully prepared with acyl chloride method. Various analytical techniques such as liquid chromatography–mass spectrometry, Fourier transform infrared spectrometry, proton and carbon nuclear magnetic resonance spectroscopy were employed to evaluate the chemical structure of the ester. The surface properties of the ester were investigated by surface tension and resonance light‐scattering techniques. The surfactant molecules are adsorbed at the water–air interface in different adsorption states, i.e., state 1 and 2. The dynamic adsorption behavior was studied by combining experimental results and a reorientation model. The molar fraction of solvent decreased, while the molar fraction of surfactant molecules increased with increasing ester concentration at the surface layer. The adsorption value of state 1 presented a unimodal shape and the adsorption value of state 2 presented an s‐shape with the increase in surface pressure. The free energy of adsorption is −36.06 kJ mol −1, more negative than the free energy of micellization (−29.69 kJ mol −1 ), it is actually easier for surfactant molecules to adsorb on the air–water interface.